2023
DOI: 10.3389/fphys.2023.1224009
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of candidate chemosensory receptors in the bean bug Riptortus pedestris (Hemiptera: Alydidae) and the functional verification of its odorant receptor co-receptor (Orco) in recognizing aggregation pheromone

Abstract: A sophisticated and sensitive olfactory system plays a vital role in the survival and reproduction of insects. Chemosensory receptors are indispensable for the molecular recognition and discrimination of semiochemicals. Riptortus pedestris is a notorious pest of legume plants, resulting in yield losses and quality decreases in soybeans. It is well accepted that R. pedestris highly relies on its olfactory system in detecting aggregation pheromones, host volatiles, and pesticides; however, little research focuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…The genomic and transcriptomic data of R. pedestris have been published to study its development, chemosensory genes, and insecticide resistance [20,[23][24][25]41,42]. Previous qRT-PCR studies on R. pedestris commonly employed universal reference genes for insect species [23][24][25][26]. Nevertheless, the use of inappropriate ones may result in misinterpretation of data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genomic and transcriptomic data of R. pedestris have been published to study its development, chemosensory genes, and insecticide resistance [20,[23][24][25]41,42]. Previous qRT-PCR studies on R. pedestris commonly employed universal reference genes for insect species [23][24][25][26]. Nevertheless, the use of inappropriate ones may result in misinterpretation of data.…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al identified numerous differentially expressed genes implicated in wing formation through a comparative analysis of the transcriptomes of R. pedestris eggs, first-, second-, third-, fourth-, and fifth-instar nymphs, as well as adults [23]. Moreover, Liu et al [24] and Li et al [25] conducted a transcriptional analysis of gene expression in the antennae of R. pedestris and identified several genes potentially involved in olfactory and taste transduction. The quantitative assessment of gene expression not only enhances the comprehension of the molecular mechanisms associated with insect development, stress response, and behavioral regulation in R. pedestris but also holds the potential to reveal novel targets for effective pest control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation